The efficacy and safety of levetiracetam in paediatric patients treated with chemotherapeutic agents for haematologic disorders. (12th February 2014) - Bayram, Erhan; Topcu, Yasemin; Tufekci, Ozlem; Karaoglu, Pakize; Yis, Uluc; Oren, Hale; Kurul, Semra Hiz
<x xml:space="preserve">Abstract</x> Aim We aimed to describe the efficacy and safety of levetiracetam in paediatric patients receiving chemotherapy for haematologic disorders. Methods Children with haematologic disorders who were receiving chemotherapy agents and developed seizure during treatment and treated with levetiracetam were included in the study. The clinical data of the patients were retrospectively evaluated. Primary haematologic diagnosis, chemotherapeutic agents, age at first seizure, seizure type, interictal electroencephalography findings, magnetic resonance imaging findings, response to the levetiracetam treatment, dose of levetiracetam, levetiracetam side effects and treatment period were recorded. Results Ten patients with a mean age 12.4 ± 2.96 years were included in the study. Possible triggering factors for seizures were chemotherapeutic agents in 60% (n = 6), posterior reversible encephalopathy syndrome in 20% (n = 2) and central nervous system involvement of the primary disease in 20% (n = 2). Nine patients received levetiracetam monotherapy, and one patient received levetiracetam that was added on oxcarbazepine due to the intractable seizures. The mean duration of antiepileptic treatment that overlapped with chemotherapy was 7.3 ± 3.5 months. Nine patients (90%) were seizure free after levetiracetam monotherapy, and one patient (10%) had ≥50% seizure reduction after levetiracetam who was previously treated with oxcarbazepine. No side effects were observed for levetiracetam during treatment. Conclusion Levetiracetam treatment is safe and effective to prevent seizures in children receiving chemotherapy for haematologic disorders.